Who Drove and Burst the Tech Bubble? - GRIFFIN, JOHN M.; HARRIS, JEFFREY H.; SHU, TAO; TOPALOGLU, SELIM (Journal of Finance, 2011)
ABSTRACT From 1997 to March 2000, as technology stocks rose more than five‐fold, institutions bought more new technology supply than individuals. Among institutions, hedge funds were the most aggressive investors, but independent investment advisors and mutual funds (net of flows) actively invested the most capital in the technology sector. The technology stock reversal in March 2000 was accompanied by a broad sell‐off from institutional investors but accelerated buying by individuals, particularly discount brokerage clients. Overall, our evidence supports the bubble model of Abreu and Brunnermeier (2003), in which rational arbitrageurs fail to trade against bubbles until a coordinated selling effort occurs.